Endothelial Dysfunction Biomarkers in Chronic Hypertension and Their Clinical : Penanda Biologis Disfungsi Endotel pada Hipertensi Kronis dan Aplikasinya Klinis - Zina Lafta Hassan; Saman Rafeeq Abdullah; Sabaa Abd alsalam Kareem; Osama A. Mohsein (Academia Open, 2025)
Background: Endothelial dysfunction is a key factor linking hypertension, inflammation, and metabolic disturbances, yet its biomarker profile in chronic hypertension remains insufficiently clarified. Specific Background: The vascular endothelium regulates vascular tone and homeostasis, but persistent hypertension alters its function through inflammatory and oxidative pathways. Knowledge Gap: Although endothelial impairment is recognized in cardiovascular disease, comprehensive biomarker-based evidence in chronic hypertensive patients is limited, particularly in Middle Eastern populations. Aim: This study aimed to assess endothelial dysfunction biomarkers and their correlations with metabolic and inflammatory markers in patients with chronic hypertension. Results: A case-control study involving 100 hypertensive patients and 50 healthy controls revealed significantly elevated endothelin-1, VCAM-1, ICAM-1, E-selectin, CRP, IL-6, TNF-α, MDA, total cholesterol, LDL-C, triglycerides, and fasting glucose, alongside reduced NO, SOD, and HDL-C (p < 0.001). Biomarker levels correlated positively with age, BMI, hypertension duration, and inflammatory indices. Novelty: This study provides integrative evidence linking vascular, inflammatory, and metabolic biomarkers with disease severity, emphasizing endothelial dysfunction as a multifactorial process in hypertension. Implications: The findings underscore the potential of biomarker profiling to improve risk stratification, early detection of complications, and the design of targeted therapeutic interventions in chronic hypertension.Highlight : Hypertensive patients show higher endothelial dysfunction biomarkers and lower nitric oxide. Inflammation and oxidative stress are strongly associated with hypertension progression. Lipid and glucose abnormalities increase cardiovascular complication risks. Keywords : Endothelial Dysfunction Biomarkers, Chronic Hypertension, Clinical Implications, Inflammation, Lipid Abnormalities